2019
DOI: 10.3390/ijms20030487
|View full text |Cite
|
Sign up to set email alerts
|

Zn2+ Aggravates Tau Aggregation and Neurotoxicity

Abstract: Alzheimer′s disease (AD) is a neurodegenerative disease with high morbidity that has received extensive attention. However, its pathogenesis has not yet been completely elucidated. It is mainly related to β-amyloid protein deposition, the hyperphosphorylation of tau protein, and the loss of neurons. The main function of tau is to assemble tubulin into stable microtubules. Under pathological conditions, tau is hyperphosphorylated, which is the major component of neurofibrillary tangles (NFT) in AD. There is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
3
27
0
Order By: Relevance
“…These data suggest that the generation of tau filaments is a disulfide bond mediated process while oxidation modulates the ability to self-assemble. Consistent with this thought it was recently shown that Zn 2+ interacts with the cysteine residue of a truncated version of tau containing only the third repeat unit of the microtubule-binding domain accelerating its aggregation rate and toxicity in a Neuro-2A cell line [108]. A more direct role for oxidative stress in tau assembly was demonstrated upon administration of the anti-oxidants 2,4-disulfonyl ␣-phenyl tertiary butyl nitrone and N-acetylcysteine which reduced immunoreactivity against tau oligomers [109].…”
Section: Oxidation Of Tau Affects Filament Assemblysupporting
confidence: 58%
“…These data suggest that the generation of tau filaments is a disulfide bond mediated process while oxidation modulates the ability to self-assemble. Consistent with this thought it was recently shown that Zn 2+ interacts with the cysteine residue of a truncated version of tau containing only the third repeat unit of the microtubule-binding domain accelerating its aggregation rate and toxicity in a Neuro-2A cell line [108]. A more direct role for oxidative stress in tau assembly was demonstrated upon administration of the anti-oxidants 2,4-disulfonyl ␣-phenyl tertiary butyl nitrone and N-acetylcysteine which reduced immunoreactivity against tau oligomers [109].…”
Section: Oxidation Of Tau Affects Filament Assemblysupporting
confidence: 58%
“…In relation to the development of neurodegenerative diseases, transition metals are involved in the formation of cytotoxic protein aggregates from misfolded proteins as shown for PD, AD, HD, and ALS 67–72 . Moreover, transition metal accumulation and metal metabolism dysfunction have been shown for postmortem brain tissue of PD and AD patients 73–75 .…”
Section: Novel Approaches For Neurodegenerative Disease Treatmentmentioning
confidence: 99%
“…92 Zn 2+ has also been shown to accelerate the aggregation of TP. 95 99 Huang et al (2014) studied the effects of Zn 2+ on TP in the presence and absence of Zn 2+ and the results suggest that Zn 2+ clearly causes aggregation of TP in vitro, and even the fact that removing Zn 2+ seems to remove the toxicity of TP. 96 The Zn 2+ binding site has not been clearly elucidated, though some have proposed that a cysteine residue is involved.…”
Section: Tau Proteinmentioning
confidence: 99%